HUBUNGAN KETERSEDIAAN OBAT BPH DAN KUALITAS PELAYANAN FARMASI TERHADAP KEPUASAN PASIEN DI RS NATAMA TEBING TINGGI - Doli Catur Utomo; Ermi Girsang; Sri Lestari Ramadhani Nasution (Smart Education, 2026)
This study examines the relationship between the availability of Benign Prostatic Hyperplasia (BPH) medication and the quality of pharmaceutical services on patient satisfaction at Natama Tebing Tinggi Hospital. BPH is a common disease in elderly men and can reduce quality of life, requiring ongoing therapy and good pharmaceutical support. This study used a quantitative method with an observational analytical design and a cross-sectional approach in outpatients with BPH. Data were collected through questionnaires and statistically analyzed to determine the relationship between variables. The results showed that adequate medication availability and optimal pharmaceutical service quality were positively associated with patient satisfaction. Therefore, improving medication management and the quality of pharmaceutical services needs to be a priority for hospitals to increase patient satisfaction.